2015
DOI: 10.1016/j.neuropsychologia.2015.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Unitization supports lasting performance and generalization on a relational memory task: Evidence from a previously undocumented developmental amnesic case

Abstract: Recently, the amnesic case D.A. was shown to circumvent his relational memory impairments, as observed in the transverse patterning (TP) task, using a self-generated unitization strategy, and such performance benefits were maintained over extended delays (Ryan et al., 2013). "Unitization" encourages fusing of distinct items, through an action, into a single unit from which the relations among the items may then be derived. Here, we provide the first documentation of the developmental amnesic case, N.C., who pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 34 publications
10
38
0
Order By: Relevance
“…The results of an updated neuropsychological evaluation performed when NC was 20‐yr old are shown in Table . As described in D'Angelo et al (), these results confirmed that in the context of average intelligence, N.C. was severely impaired on tests of delayed recall. N.C. also performed below expected levels on tests of working memory and more complex aspects of visuospatial processing (e.g., recognizing faces, integrating details into a complex figure).…”
Section: Methodssupporting
confidence: 86%
See 4 more Smart Citations
“…The results of an updated neuropsychological evaluation performed when NC was 20‐yr old are shown in Table . As described in D'Angelo et al (), these results confirmed that in the context of average intelligence, N.C. was severely impaired on tests of delayed recall. N.C. also performed below expected levels on tests of working memory and more complex aspects of visuospatial processing (e.g., recognizing faces, integrating details into a complex figure).…”
Section: Methodssupporting
confidence: 86%
“…N.C. has previously been described in D'Angelo et al (). Briefly, N.C. is a young, right‐handed man with 14 yr of education, including high school and 1 yr of technical college.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations